Protocol for the Northern Manhattan Diabetes Community Outreach Project. A randomised trial of a community health worker intervention to improve diabetes care in Hispanic adults. Issue 2 (26th March 2012) - Palmas, Walter; Teresi, Jeanne A; Findley, Sally; Mejia, Miriam; Batista, Milagros; Kong, Jian; Silver, Stephanie; Luchsinger, Jose A; Carrasquillo, Olveen
Abstract : Objective: Hispanics in the USA are affected by the diabetes epidemic disproportionately, and they consistently have lower access to care, poorer control of the disease and higher risk of complications. This study evaluates whether a community health worker (CHW) intervention may improve clinically relevant markers of diabetes care in adult underserved Hispanics. Methods and analysis: The Northern Manhattan Diabetes Community Outreach Project (NOCHOP) is a two-armed randomised controlled trial to be performed as a community-based participatory research study performed in a Primary Care Setting in Northern Manhattan (New York City). 360 Hispanic adults with poorly controlled type 2 diabetes mellitus (haemoglobin A1c >8%), aged 35–70 years, will be randomised at a 1:1 ratio, within Primary Care Provider clusters. The two study arms are (1) a 12-month CHW intervention and (2) enhanced usual care (educational materials mailed at 4-month intervals, preceded by phone calls). The end points, assessed after 12 months, are primary = haemoglobin A1c and secondary = blood pressure and low-density lipoprotein-cholesterol levels. In addition, the study will describe the CHW intervention in terms of components and intensity and will assess its effects on (1) medication adherence, (2) medication intensification, (3) diet and (4) physical activity. Ethics and dissemination: All participants will provide informed consent; the study protocol has been approved by the Institutional Review Board of Columbia University Medical Center. CHW interventions hold great promise in improving the well-being of minority populations who suffer from diabetes mellitus. The NOCHOP study will provide valuable information about the efficacy of those interventions vis-à-vis clinically relevant end points and will inform policy makers through a detailed characterisation of the programme and its effects. Clinical trial registration number: NCT00787475 at clinicaltrials.gov.